[(eta(6)-p-Pr(i)C6H4Me)(2)Ru2Mo2O6(OMe)(4)]: a new tetranuclear mixed-metal oxo cluster presenting a cube-based chair structure - Plasseraud, Laurent; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 1999)
The title complex was obtained by reaction of [(eta(6)-p-Pr'C6H4Me)(4)Ru4Mo4O16] with methanol in the presence of p-hydroquinone. It contains an Mo2Ru2O2(OMe)(4) core consisting of two Mo2RuO(OMe)(3) half-cubes fused together to form a choir-like structure. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: crystal structures; oxo clusters; arene complexes; ruthenium complexes; molybdenum complexes; AMPHIPHILIC ORGANORUTHENIUM OXOMOLYBDENUM; X-RAY STRUCTURES; CRYSTAL-STRUCTURES; COMPLEXES; DERIVATIVES; OXOVANADIUM